Risk Factors for Stiff Left Atrial Physiology 1 Year After Catheter Ablation of Atrial Fibrillation - Lee, Jae-Hyuk; Kwon, Oh-Seok; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Physiology, 2021)
Catheter ablation is the most effective rhythm control method for patients with atrial fibrillation (AF), however, it inevitably causes atrial tissue damage. We previously reported that AF catheter ablation (AFCA) increases left atrial (LA) pressure without changes in symptom scores. We hypothesized that extensive LA ablation increased the risk of stiff LA physiology. We included 1720 patients (69.1% male, 60.0 [53.0–68.0] years old, 66.2% with paroxysmal AF) who underwent de novo AFCA and echocardiography before and 1-year after procedure. Stiff LA physiology was defined, when the amount of estimated pulmonary arterial pressure increase between the pre-procedural and the 1-year post-procedural follow-up echocardiography was >10mmHg, and when right ventricular systolic pressure was >35mmHg at 1-year follow-up echocardiography. Failed rhythm control within 1-year was defined as recurrent AF despite using anti-arrhythmic drugs or cardioversion within a year of AFCA. We explored the incidence and risk factors for stiff LA physiology and the rhythm outcome of AFCA. Among the 1720 patients, 64 (3.7%) had stiff LA physiology 1-year after AFCA. Stiff LA physiology was independently associated with diabetes (odd ratio [OR], 2.36 [95% CI, 1.14–4.87], p=0.020), E/Em (OR, 1.04 [95% CI, 1.00–1.10], p=0.049), LA pulse pressure (Model 2: OR, 1.05 [95% CI, 1.00–1.11], p=0.049), low LA voltage (OR, 0.36 [95% CI, 0.18–0.74], p=0.005), empirical extra-PV LA ablation (OR, 2.60 [95% CI, 1.17–5.74], p=0.018), and RF ablation duration (Model 2: OR, 1.02 [95% CI, 1.01–1.03], p=0.003). Although the incidence of post-AFCA stiff LA physiology was 3.7% and most of the cases were subclinical, empirical extra-PV ablation was associated with this undesirable condition. In addition, patients who had low mean LA voltage before AFCA could be susceptible to stiff LA physiology.